(6-x)(4-x)=30

Simple and best practice solution for (6-x)(4-x)=30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6-x)(4-x)=30 equation:


Simplifying
(6 + -1x)(4 + -1x) = 30

Multiply (6 + -1x) * (4 + -1x)
(6(4 + -1x) + -1x * (4 + -1x)) = 30
((4 * 6 + -1x * 6) + -1x * (4 + -1x)) = 30
((24 + -6x) + -1x * (4 + -1x)) = 30
(24 + -6x + (4 * -1x + -1x * -1x)) = 30
(24 + -6x + (-4x + 1x2)) = 30

Combine like terms: -6x + -4x = -10x
(24 + -10x + 1x2) = 30

Solving
24 + -10x + 1x2 = 30

Solving for variable 'x'.

Reorder the terms:
24 + -30 + -10x + 1x2 = 30 + -30

Combine like terms: 24 + -30 = -6
-6 + -10x + 1x2 = 30 + -30

Combine like terms: 30 + -30 = 0
-6 + -10x + 1x2 = 0

Begin completing the square.

Move the constant term to the right:

Add '6' to each side of the equation.
-6 + -10x + 6 + x2 = 0 + 6

Reorder the terms:
-6 + 6 + -10x + x2 = 0 + 6

Combine like terms: -6 + 6 = 0
0 + -10x + x2 = 0 + 6
-10x + x2 = 0 + 6

Combine like terms: 0 + 6 = 6
-10x + x2 = 6

The x term is -10x.  Take half its coefficient (-5).
Square it (25) and add it to both sides.

Add '25' to each side of the equation.
-10x + 25 + x2 = 6 + 25

Reorder the terms:
25 + -10x + x2 = 6 + 25

Combine like terms: 6 + 25 = 31
25 + -10x + x2 = 31

Factor a perfect square on the left side:
(x + -5)(x + -5) = 31

Calculate the square root of the right side: 5.567764363

Break this problem into two subproblems by setting 
(x + -5) equal to 5.567764363 and -5.567764363.

Subproblem 1

x + -5 = 5.567764363 Simplifying x + -5 = 5.567764363 Reorder the terms: -5 + x = 5.567764363 Solving -5 + x = 5.567764363 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + x = 5.567764363 + 5 Combine like terms: -5 + 5 = 0 0 + x = 5.567764363 + 5 x = 5.567764363 + 5 Combine like terms: 5.567764363 + 5 = 10.567764363 x = 10.567764363 Simplifying x = 10.567764363

Subproblem 2

x + -5 = -5.567764363 Simplifying x + -5 = -5.567764363 Reorder the terms: -5 + x = -5.567764363 Solving -5 + x = -5.567764363 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + x = -5.567764363 + 5 Combine like terms: -5 + 5 = 0 0 + x = -5.567764363 + 5 x = -5.567764363 + 5 Combine like terms: -5.567764363 + 5 = -0.567764363 x = -0.567764363 Simplifying x = -0.567764363

Solution

The solution to the problem is based on the solutions from the subproblems. x = {10.567764363, -0.567764363}

See similar equations:

| 6z-8z+3=0 | | (6-x)x(4-x)=30 | | n-2/2=-7 | | 17.6=2.2*n | | 210=3(-7x-2)-6x | | kx^2+10x-8=0 | | 2p-q=7 | | -4(-7n+5)=1 | | 1/2(x+3)^2=5 | | 0.5x+4=0.75(2x-8) | | 7n=-77 | | -21=56 | | 6-6x+4=4 | | 1/2(x+3)2=5 | | 9x-5y=3 | | 10(a+6)=1 | | 4X+3=5(X-2) | | y+4+6y-5=180 | | 16=-6k+4+4k | | n-13=-6 | | 16=x/14 | | y=-3x-16 | | 4x^2+y=0 | | B^2-1=-18 | | -35-3x=5-9x | | 6v(v+9)=1 | | 6(5a-1)+11= | | 3-a/2=5 | | 2x^3+x^2-28x=0 | | -15p-55p=1 | | -15p-55p=11 | | 3x-5y-16=0 |

Equations solver categories